2001
DOI: 10.1211/0022357011776171
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by carbapenem antibiotic imipenem of intestinal absorption of valproic acid in rats

Abstract: The concomitant use of carbapenem antibiotics with valproic acid has been prohibited because panipenem induced a decrease in plasma concentration of valproic acid in epileptic patients during valproic acid therapy. To clarify the possible mechanism of the carbapenem-valproic acid interaction, we investigated the effect of imipenem on the pharmacokinetic behaviour of valproic acid in rats. Co-administration of imipenem (30 mg kg(-1), i.v.) induced a decrease in the peak plasma concentration of valproic acid aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…In contrast, the other three proposed mechanisms, namely, 1) interaction at intestinal absorption process, 2) interaction at enterohepatic circulation process, and 3) interaction at blood cell distribution process (Mori et al, 2007), are less likely in humans than the interaction at the VPA-G hydrolysis process. Torii et al (2001) reported that the C max and area under the curve of VPA were decreased by 50 to 60% after oral administration of VPA with imipenem and PAPM treatment in rats, suggesting that the intestinal absorption of VPA might be inhibited by carbapenems. However, the plasma level of VPA was also decreased at later time points even after intravenous administration of VPA with the carbapenems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the other three proposed mechanisms, namely, 1) interaction at intestinal absorption process, 2) interaction at enterohepatic circulation process, and 3) interaction at blood cell distribution process (Mori et al, 2007), are less likely in humans than the interaction at the VPA-G hydrolysis process. Torii et al (2001) reported that the C max and area under the curve of VPA were decreased by 50 to 60% after oral administration of VPA with imipenem and PAPM treatment in rats, suggesting that the intestinal absorption of VPA might be inhibited by carbapenems. However, the plasma level of VPA was also decreased at later time points even after intravenous administration of VPA with the carbapenems.…”
Section: Discussionmentioning
confidence: 99%
“…Some mechanisms related to absorption, distribution, and metabolism of VPA have been proposed (Kojima et al, 1998;Yamamura et al, 1999;Torii et al, 2001;Nakajima et al, 2004;Omoda et al, 2005). Among them, metabolism in the liver has been considered to be the most important for interaction, based on the following findings.…”
Section: Introductionmentioning
confidence: 99%
“…Torii et al 19 proposed that the inhibition of intestinal absorption of valproic acid by carbapenem antibiotics might be a mechanism for the drug interaction in rats. By utilizing the in situ vascular and luAm J Health-Syst Pharm-Vol 67 Aug 1, 2010 minal perfused small intestine, the absorption of valproic acid from the luminal to the vascular perfusate was confirmed to be decreased in the presence of imipenem.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the interaction between VPA and CBPMs, the following mechanisms have been proposed: 1) inhibition of intestinal VPA absorption by CBPMs (Torii et al, 2001(Torii et al, , 2002, 2) interruption of enterohepatic circulation of VPA by CBPMs (Kojima et al, 1998), 3) increased partition of VPA into erythrocytes by CBPMs (Omoda et al, 2005;Ogawa et al, 2006), 4) elevation of UDP-GA levels by CBPMs (Yamamura et al, 1999(Yamamura et al, , 2000, 5) induction of UGT by CBPMs (Mori and Mizutani, 2007), and 6) inhibition of deconjugation of VPA-glucuronide (VPA-G) by CBPMs (Nakajima et al, 2004;Nakamura et al, 2008). However, most of the previously proposed mechanisms (mechanisms 1-5) may not solely explain the interaction observed under clinical conditions for the following reasons: with mechanism 1, the interaction observed after intravenous administration of VPA (Clause et al, 2005;Coves-Orts et al, 2005;Spriet et al, 2007) cannot be accounted for.…”
Section: Introductionmentioning
confidence: 99%